2016
DOI: 10.1038/ncomms13045
|View full text |Cite|
|
Sign up to set email alerts
|

EpCAM-dependent extracellular vesicles from intestinal epithelial cells maintain intestinal tract immune balance

Abstract: How the intestinal tract develops a tolerance to foreign antigens is still largely unknown. Here we report that extracellular vesicles (EVs) with TGF-β1-dependent immunosuppressive activity are produced by intestinal epithelial cells (IECs) under physiological conditions. Transfer of these EVs into inflammatory bowel disease (IBD) mice induced by dextran sulfate sodium salt decreases IBD severity by inducing regulatory T cells and immunosuppressive dendritic cells. In contrast, decreased endogenous EV producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 44 publications
2
111
0
Order By: Relevance
“…Hydrolyzing ATP to Adenosine In Vitro Our previous study had shown that EVs from murine spleens (Sp-EVs) contain transforming growth factor (TGF)-b1 (Jiang et al, 2016). Accordingly, we tested whether Sp-EVs could inhibit CD8 + T cell proliferation in vitro.…”
Section: Cd19 + Evs Inhibit Cd8 + T Cell Proliferation Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrolyzing ATP to Adenosine In Vitro Our previous study had shown that EVs from murine spleens (Sp-EVs) contain transforming growth factor (TGF)-b1 (Jiang et al, 2016). Accordingly, we tested whether Sp-EVs could inhibit CD8 + T cell proliferation in vitro.…”
Section: Cd19 + Evs Inhibit Cd8 + T Cell Proliferation Bymentioning
confidence: 99%
“…For EV or iEBV flow cytometry analysis, EVs or iEBVs were coated onto 4-mm-diameter aldehyde-sulfate latex beads, as described previously (Jiang et al, 2016). The EV-coated beads were stained with the corresponding fluorescence-labeled Abs for 30 min on ice.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Kanazawa et al found that TGF-b2 and TGF-b3 expression was elevated in lamina propria lymphocytes of active UC and CD patients [20]. Moreover, the intestinal epithelium can produce TGF-b-containing extracellular vesicles [21]. Therefore, TGF-b levels are increased in IBD tissues, but this may not be sufficient to counteract the ongoing inflammation.…”
Section: Tgf-b In Ibd Tgf-b Productionmentioning
confidence: 99%
“…A recent study revealed that TGF-b-containing extracellular vesicles released by epithelial cells induced Treg differentiation and inhibited colitis by binding to EpCAM ? epithelial cells [21]. Therefore, epithelial cells also play an important role in immune homeostasis in a TGF-b-dependent manner.…”
Section: Epithelium and Extracellular Matrixmentioning
confidence: 99%
“…Similar to early beliefs about EVs, non-coding RNA was also originally thought to be cellular waste and was disregarded for its assumed lack of a biological role (10). Ironically, both EVs and non-coding RNAs are now implicated in various disease states including cancer (11, 12), cardiovascular (13) and neuronal diseases (14). We refer the reader to the many excellent reviews on therapeutic EVs (1518).…”
Section: Introductionmentioning
confidence: 99%